Analisis Pengawasan Pengelolaan Keuangan Negara Terhadap Prinsip Transparansi dan Akuntabilitas Berdasarkan Regulasi Pengelolaan Keuangan Desa - Erdianti, Nela; Ramadhan, Muhammad Rizqi Hilal Ilham (Universitas Sultan Ageng Tirtayasa, 2023)
In the 1945 Constitution it is explained that the government of the Republic of Indonesia recognizes the existence of villages and customary rights and respects diversity and provides constitutional protection to all village communities. The village government is responsible for managing village finances independently as stipulated in Law Number 6 of 2014 concerning Villages. The responsibility given is not only for village financial management but also includes assets owned and village income in order to improve the quality of life of village communities. The problem that will arise in the use of village finances is the emergence of fraud and corruption committed by village officials or the village government. Therefore, it is necessary to know how the position of village finance is in supervising state finances and the implementation of supervision of villagefinancial management based on village financial regulations in Indonesia. This study uses a descriptive analysis method, using a normative juridical approach and a case study. The results of the research show that currently there is no law or legal provisions that regulate precisely which explains that village finances are part of state or regional finances. Related to village finances, it is only regulated in the source of funding obtained for the benefit of the village. Regarding village financial funding sources, it is regulated in article 72 of Law Number 6 of 2014. In order to make it clearer that village finances are part of state finances, new legal encouragement and provisions are needed which explain precisely that village finances are part of state finances. Arrangements for the implementation of supervision of state financial management are contained in Permendagri no 73 of 2020 through several stages, namely planning, implementation, reporting and follow-up supervision.